Asessmen Perkembangan Anak Autisme dalam Pendidikan Inklusif di SKH 01 Nurbayan Kelas 5 - Retno Andriyani; Amanda Putri Humaeroh; Siti Sholikha; Virli Ibtisam Naura Azis; Sabila Putri Andriani (Lembaga Pengembangan Kinerja Dosen, 2026)
Inclusive education requires a comprehensive understanding of the characteristics and learning needs of students with special needs, particularly children with autism spectrum disorders. Assessment plays a crucial role as an initial step in identifying abilities, challenges, and educational needs to design appropriate learning interventions. This study aims to describe the results of developmental assessment of a child with autism in an inclusive education setting at SKH 01 Nurbayan Grade 5. This research employs a descriptive approach using assessment instruments that cover five developmental domains: social interaction, communication, behavior, emotional regulation, and sensory perception. The results reveal significant difficulties in social communication, including low social interest, delayed language development, limited nonverbal communication, and the presence of repetitive behaviors. Emotional regulation remains underdeveloped, and sensory processing issues are evident. These findings indicate that children with autism require individualized, structured, and needs-based educational interventions. Therefore, assessment serves as a fundamental basis for planning effective and sustainable inclusive learning programs.